2022
DOI: 10.1002/ejic.202200202
|View full text |Cite
|
Sign up to set email alerts
|

Shape Regulation of CeO2 Nanozymes Boosts Reaction Specificity and Activity

Abstract: Among reported nanozymes, CeO 2 seems to be the only transition metal oxide that can mimic phosphatase and peroxidase by catalyzing substrate dephosphorylation and oxidation (with H 2 O 2 ). However, no consensus on the key Ce species was reached in the literature using spherical CeO 2 enclosed by ( 111) and (100) surfaces, not to mention the further control of its reaction specificity. In this study, octahedral and cubic CeO 2 preferentially terminated by ( 111) and (100) surfaces were found to exhibit high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…On the other hand, although facet-dependent enzyme-like activities have been reported for CeO 2 (and other nanozymes), only a few research groups have focused on the control of specificity/selectivity among enzymatic reactions, which is a very challenging issue in the field. Single-atom nanozymes were recently demonstrated to tune the selective activation between two different substrates, H 2 O 2 and O 2 , for the control of their POD-like and oxidase-like activities. , Our group also found that CeO 2 nanozymes in different shapes can interact very differently with H 2 O 2 and phosphate-containing molecules and hence the control of their reaction specificity between the POD-like and phosphatase-like reactions. , In comparison, regulating a single substrate and hence the control of reaction specificity over a given material is an even greater challenge. To the best of our knowledge, the Tremel group is the only group so far regulating H 2 O 2 on mesoporous CeO 2 nanozymes for tunable POD-like and HPO-like activities, although the reaction specificity is unsatisfactory .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, although facet-dependent enzyme-like activities have been reported for CeO 2 (and other nanozymes), only a few research groups have focused on the control of specificity/selectivity among enzymatic reactions, which is a very challenging issue in the field. Single-atom nanozymes were recently demonstrated to tune the selective activation between two different substrates, H 2 O 2 and O 2 , for the control of their POD-like and oxidase-like activities. , Our group also found that CeO 2 nanozymes in different shapes can interact very differently with H 2 O 2 and phosphate-containing molecules and hence the control of their reaction specificity between the POD-like and phosphatase-like reactions. , In comparison, regulating a single substrate and hence the control of reaction specificity over a given material is an even greater challenge. To the best of our knowledge, the Tremel group is the only group so far regulating H 2 O 2 on mesoporous CeO 2 nanozymes for tunable POD-like and HPO-like activities, although the reaction specificity is unsatisfactory .…”
Section: Discussionmentioning
confidence: 96%
“…45,46 Our group also found that CeO 2 nanozymes in different shapes can interact very differently with H 2 O 2 and phosphatecontaining molecules and hence the control of their reaction specificity between the POD-like and phosphatase-like reactions. 47,48 In comparison, regulating a single substrate and hence the control of reaction specificity over a given material is an even greater challenge. To the best of our knowledge, the Tremel group is the only group so far regulating H 2 O 2 on mesoporous CeO 2 nanozymes for tunable POD-like and HPO-like activities, although the reaction specificity is unsatisfactory.…”
Section: Characterization and Catalytic Testing Of Ceomentioning
confidence: 99%
“…9a). 122 Surface Ce species on the cube have a higher electron density, promoting PODlike activity with ∼10 and ∼49 times higher reactivity than those on the sphere and octahedron surfaces, respectively. Zhang's group has achieved the selectivity of nanozymes through ingenious HOMO/LUMO-mediated strategies, eliminating the need for additional modifications (Fig.…”
Section: Selective Nanomaterialsmentioning
confidence: 98%